1983
DOI: 10.4315/0362-028x-46.7.589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Restructured Chops Manufactured from Prerigor and Postrigor Pork

Abstract: Restructured chops from prerigor (P) and conventionally boned (C) pork were unsalted (U) or salted (S) with 2.0% sodium chloride (NaCl) and 0.25% sodium tripolyphosphate (STP). After storage for 5, 14 and 42 d, samples were subjectively evaluated for amount of discoloration, consumer desirability, juiciness, tenderness and flavor. Objective measurements included Hunter color difference meter readings and TBA values. Generally, objective and subjective appearance traits and flavor deteriorated (P<0.05) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…However, color scores of chopped C steaks stored for 0 and 14 days were superior (P<0.05) to the control samples that were coarse-chopped and ground. Color degradation that occurred during frozen storage is in agreement with previous research reported byMarriott et al (1983) and Huffman et al(1981). Data in 'Igble 2 provide an objective measurement of color by the Hunter Color Difference Meter.…”
supporting
confidence: 93%
“…However, color scores of chopped C steaks stored for 0 and 14 days were superior (P<0.05) to the control samples that were coarse-chopped and ground. Color degradation that occurred during frozen storage is in agreement with previous research reported byMarriott et al (1983) and Huffman et al(1981). Data in 'Igble 2 provide an objective measurement of color by the Hunter Color Difference Meter.…”
supporting
confidence: 93%
“…This observation is in agreement with previous results that we have reported (Marriott et al 1983;1985). However, this device revealed that the C chops as well as the A chops with 0 days storage had more (P< 0.05) redness, perhaps due to the black color of the extracts in the M and S samples.…”
Section: Control Dried Applessupporting
confidence: 93%
“…Cross and Stanfield (1976), Schwartz and Mandigo (1976), Huffman et al (1981) and Marriott et al 1983 reported that this adjunct improved taste attributes. However, Neer and Mandig0 (1977), Ockerman and Organisciak (1979), Huffman et al (1981), and Marriott et al (1985b) have reported increased oxidation as evidenced by higher TBA values and/or color degradation with increased salt levels.…”
Section: Introductionmentioning
confidence: 95%